PENERAPAN RESTORATIVE JUSTICE DALAM UNDANG-UNDANG SISTEM PERADILAN PIDANA ANAK (STUDI KASUS PENETAPAN PENGADILAN NEGERI JAKARTA BARAT NOMOR 39/PEN.DIVERSI/PID.SUS ANAK/2019/PN.JKT.BRT) - Arilasman Cornelius (2021)
This research was conducted to complete the Thesis, as one of the requirements to get a Master of Law degree. This study discusses Restorative Justice which is part of the juvenile criminal justice system where the resolution of legal problems seen by children is resolved through thought, especially by uniting perpetrators, victims, and mediators as impartial parties to consult and find the best answers for children. Based on this description, the background of the problem of applying restorative justice in the law on the juvenile criminal justice system. the problem identification will be formulated regarding the inhibiting factors of the Public Prosecutor in resolving cases of children in conflict with the law by applying Diversion, and solutions for Public Prosecutors in resolving cases of children in conflict with the law by applying Diversion. This type of research regarding the application of restorative justice in the law on the juvenile criminal justice system is a type of research that is included in normative legal research, namely research that uses statutory regulations as a reference. In its application the application of restorative justice in the law on the juvenile criminal justice system also experiences obstacles due to the absence of an agreement between the parties, namely the parents of the victim and the perpetrator, this is because they are too concerned with the interests of their respective children, such as the perpetrator's family who does not want the child is punished, while the victim's family has a feeling of wanting to take revenge on the perpetrator and is dissatisfied if the perpetrator is not punished. This lack of understanding will certainly make the parties reluctant to make diversion efforts.